Skilled interpersonal communication : research, theory, and practice - Hargie, Owen (Routledge, 2011)
'There is a fundamental, powerful and universal desire amongst humans to interact with others. People have a deep-seated need to communicate, and the greater their ability in this regard the more satisfying and rewarding their lives will be. The contribution of skilled interpersonal communication to success in both personal and professional contexts is now widely recognised and extensively researched. As such, knowledge of various types of skills, and of their effects in social interaction, is crucial for effective interpersonal functioning.'--from books.google.com.hk.